2020
DOI: 10.1038/s41467-020-17956-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrated microbiota and metabolite profiles link Crohn’s disease to sulfur metabolism

Abstract: Gut microbial and metabolite alterations have been linked to the pathogenesis of inflammatory bowel diseases. Here we perform a multi-omics microbiome and metabolite analysis of a longitudinal cohort of Crohn's disease patients undergoing autologous hematopoietic stem cell transplantation, and investigational therapy that induces drug free remission in a subset of patients. Via comparison of patients who responded and maintained remission, responded but experienced disease relapse and patients who did not resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
118
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 86 publications
(110 reference statements)
6
118
0
Order By: Relevance
“…In IECs, H 2 S is capable of inducing genotoxic damage, and elevated levels of H 2 S can impair OXPHOS by inhibiting complex IV of the electron transfer chain (Ijssennagger et al, 2016;Saint-Georges-Chaumet and Edeas, 2016). Indicating disease relevance, an integrated microbiota and metabolite profile analysis has recently linked Crohn's disease activity to bacterial sulfur metabolism (Metwaly et al, 2020). Moreover, in IBD, an adverse microbiota-host interaction has been reported for H 2 S, with increased abundance of sulfate-reducing bacteria (i.e., H 2 S-producers) on the microbial side and a decreased expression of mitochondrial proteins involved in hydrogen sulfide detoxification on the host side (Mottawea et al, 2016).…”
Section: Mitochondria As Metabolic Integrators Of Microbial Signalsmentioning
confidence: 99%
“…In IECs, H 2 S is capable of inducing genotoxic damage, and elevated levels of H 2 S can impair OXPHOS by inhibiting complex IV of the electron transfer chain (Ijssennagger et al, 2016;Saint-Georges-Chaumet and Edeas, 2016). Indicating disease relevance, an integrated microbiota and metabolite profile analysis has recently linked Crohn's disease activity to bacterial sulfur metabolism (Metwaly et al, 2020). Moreover, in IBD, an adverse microbiota-host interaction has been reported for H 2 S, with increased abundance of sulfate-reducing bacteria (i.e., H 2 S-producers) on the microbial side and a decreased expression of mitochondrial proteins involved in hydrogen sulfide detoxification on the host side (Mottawea et al, 2016).…”
Section: Mitochondria As Metabolic Integrators Of Microbial Signalsmentioning
confidence: 99%
“…Human campylobacteriosis patients have an increased abundance of genera Escherichia, Bacteroidetes, Phascolarctobacterium, and Streptococcus in stool [3]. Comparably, microbiota sequencing data from cross-sectional IBD patients showed that IBD is associated with dysbiosis characterizing by reduced gut bacterial diversity, together with increased genera Fusobacterium, Escherichia, Faecalibacterium, Roseburia, Ruminococcaceae, Peptostreptococcaceae, Christensenellaceae, and Collinsella [88]. The changes in the gut microbiota of IBD patients show an increase in facultative anaerobes, including Escherichia coli [89], and a decrease in obligately anaerobic [90].…”
Section: Microbiota and Campylobacteriosismentioning
confidence: 98%
“…The changes in the gut microbiota of IBD patients show an increase in facultative anaerobes, including Escherichia coli [89], and a decrease in obligately anaerobic [90]. IBD patients with active disease have increased gut Enterococcus, Fusobacterium, Haemophilus, Megasphaera, Campylobacter, while Roseburia, Christensenellaceae, Oscillibacter, and Odoribacter are enriched in the gut of IBD patients with inactive disease [88]. Although increasing evidence supports the role of microbiota promoting C. jejuni infection or other enteritis, additional studies are much needed.…”
Section: Microbiota and Campylobacteriosismentioning
confidence: 99%
See 1 more Smart Citation
“…To this point, the gut microbiome has been demonstrated in recent years to facilitate detection of disease [30][31][32][33][34]; classification of disease subtypes and progression stages [35][36][37]; prediction of clinical outcomes and treatment efficacy [38][39][40][41][42]; personalized nutrition by prediction of postprandial glycemic response [43][44][45];…”
Section: Introductionmentioning
confidence: 99%